Discharge against medical advice at the adult accident and emergency department in a tertiary hospital of a developing nation - Ekwedigwe, Henry Chinedum; Edeh, Anthony Jude; Nevo, Anthony Chigozie; Ekwunife, Remigius Tochukwu (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The goals of health care provision include that it be accessible, acceptable, affordable and adequate. Discharge against medical advice (DAMA) is a failure of proper health care provision as there is disagreement arising from dissatisfaction with provided health care. DAMA is common in our sub-region because of many reasons; these includes ignorance, financial constraint of the patient, beliefs in unorthodox care and patients feeling that they are well when their caregivers do not think so. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The objectives of this study are to determine the incidence, method of documentation of DAMA in the case notes and patients reasons for DAMA in our tertiary health institution. The A&E of any hospital in our environment attracts public criticism when there is dissatisfaction with services and DAMA when not handled well can lead to justifiable criticisms and/or litigations. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This is a retrospective study. It was carried out at the adult accident and emergency department of Enugu state university of technology teaching hospital Enugu. Duration of the study was from January 2017 to December 2018. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. A total of 8,152 patients were seen in the accident and emergency during this period. One hundred and seventy one (171) case notes were retrieved and reviewed for the study, DAMA rate of 2.1% was obtained. Fifty one folders (29.8%) did not have reason for the DAMA documented in them. The commonest reason for the DAMA was to seek traditional medical care with frequency of 17.5%. This was closely followed by financial constraint with 15.8%. Documentation for DAMA was done directly in the case notes. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The incidence of DAMA from this study is similar to what is obtainable from other local studies, financial constraint on the patients and seeking alternative medical treatment were the commonest reasons for DAMA in our sub-region. Also, the documentation for the DAMA in this study was poorly done.